EMPOWERMENT OF BUPDA REFORM ACCESS IN VILLAGE LAND ASSET MANAGEMENT IN BALI - I Wayan Kartika Jaya Utama (Warmadewa Press, 2022)
The efforts to reduce poverty through increasing the role of traditional villages are very appropriate to do especially in Bali. Based on the mandate of the Regional Regulation Province Bali Number 4 of 2019 Regarding Traditional Villages, the Poh Bergong Traditional Village through a perm formed Utsaha Padruwen Desa Adat (BUPDA) managed by the traditional village. This study aims to examine the implementation of BUPDA institutions in the management and utilization of customary village land assets in Bali. The research method used is normative legal research using a statutory approach and a conceptual approach. The results of the study indicate that the development of BUPDA management uses the objective of access reform with the concept of Tri Hita Karana, the implementation of BUPDA in the management of access reform which aims to prosper the indigenous peoples and relieve the person of the community in carrying out the custom.